Ionic relationships between macronutrients and sodium in parsley under nutrient solutions prepared with brackish water - Salimo M. H. Muchecua; José A. Santos Júnior; Sirleide M. de Menezes; Gerônimo F. da Silva; Lucia H. G. Chaves; Ruana I. F. Cruz (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The concentration and nature of ions directly influence ionic relationships between macronutrients and sodium, especially in the context of plants grown under saline conditions. The goal of this study was to analyze the efficiency of use of N, P, K, Ca, Mg, and S, the efficiency of Na accumulation, and the relationships between Ca+2, Mg+2, Na+, and K+ after analysis of parsley, cultivar Graúda Portuguesa, plant tissues exposed to nutrient solutions prepared with brackish water with different cationic natures. The treatments consisted of exposing plants to nutrient solutions (ECns = 1.7, 2.7, 3.7, 4.7, 5.7, and 6.7 dS m-1) prepared with brackish water obtained by solubilizing different salts, NaCl, CaCl2.2H2O, MgCl2.6H2O, and KCl in supply water (ECw = 0.12 dS m-1). Two cultivation cycles were conducted, adopting a completely randomized experimental design in both (6 × 4 factorial scheme), with four replicates. The efficiency of the use of macronutrients and sodium accumulation was more affected by the cationic nature of the water at the highest concentration levels. Except for the Ca+2 - Mg+2 ratio, all other cationic ratios were affected by the increase in the concentration of salts in the nutrient solution.